Comparative study of benign and malignant tumor of the ovary. - Dias, M F; Pereira, H S; Sousa, L A; Torgal, I R; De Oliveira, C F (Acta Médica Portuguesa, 1997)
This study concerns the evaluation of epidemiologic, clinical and laboratory parameters and the comparison of the multiple parameters between benign and malignant tumors of the ovary to establish significant criteria allowing a Malignant Risk Index to be defined. The incidence of ovarian cancer was higher among post-menopausal women with no use of oral contraceptives. There was no correlation between sterility, infertility or nulliparity and ovarian cancer. The age at menarche, menopause or first term delivery showed no influence on the risk of ovarian cancer. The Authors verified significant differences (p < 0.001) in the levels of serum CA 125 between patients with benign ovarian tumors and patients with ovarian cancer. Those differences showed high sensitivity and specificity. Ultrasonographic criteria were difficult to interpret because of their subjectivity. However, there were significant differences concerning the size of the tumors, the bilaterality, the solid component and ascites; all these criteria were more frequent among malignant masses. It is imperative to define a high confidence degree Malignant Risk Index for ovarian tumors allowing the establishment of screening strategies applicable to risk populations.